2021
DOI: 10.1071/wr21072
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and validating koala

Abstract: Context It is notoriously difficult to estimate the size of animal populations, especially for cryptic or threatened species that occur in low numbers. Recent advances with acoustic sensors make the detection of animal populations cost effective when coupled with software that can recognise species-specific calls. Aims We assess the potential for acoustic sensors to estimate koala, Phascolarctos cinereus, density, when individuals are not identified, using spatial count models. Sites were selected where pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Mean density is commonly reported to be >0.2 per ha in koalas (Dique et al, 2004;White & Kunst, 1990) and >0.8 per ha in greater gliders (Emerson et al, 2019). Further research in Richmond Range NP should be directed at estimating density to confirm or revise the values here, using distance sampling for the greater glider (Cripps et al, 2021;Emerson et al, 2019) and arrays of audio recorders for the koala (see Law et al, 2022).…”
Section: Population Estimatesmentioning
confidence: 93%
See 1 more Smart Citation
“…Mean density is commonly reported to be >0.2 per ha in koalas (Dique et al, 2004;White & Kunst, 1990) and >0.8 per ha in greater gliders (Emerson et al, 2019). Further research in Richmond Range NP should be directed at estimating density to confirm or revise the values here, using distance sampling for the greater glider (Cripps et al, 2021;Emerson et al, 2019) and arrays of audio recorders for the koala (see Law et al, 2022).…”
Section: Population Estimatesmentioning
confidence: 93%
“…We used an estimate of adult koala density based on Law et al ( 2022 ) who used song meter arrays to estimate a density of 0.07 adult males per ha (average of three estimates) in tall forest (Bongil National Park) 170 km south of our study area. The total number of adult koalas can be derived from this based on the adult sex ratio (age class 2 and above).…”
Section: Methodsmentioning
confidence: 99%
“…Previous analyses showed that this level of survey effort (at least seven nights) has little impact on detection probability because of the high detection rate per night. Call playback in forests at 75 dB has found that call amplitude in recordings attenuates to background noise levels within 100-150 m (Charlton et al, 2012;Hagens et al, 2018), although we expect under ideal conditions this could extend to ~300 m (Law et al, 2021).…”
Section: Acoustic Samplingmentioning
confidence: 71%
“…Call playback in forests at 75 dB has found that call amplitude in recordings attenuates to background noise levels within 100–150 m (Charlton et al., 2012 ; Hagens et al., 2018 ), although we expect under ideal conditions this could extend to ~300 m (Law et al., 2021 ). Temperature could also affect bellowing frequency or sound propagation (Law et al., 2018 ), and we account for this by modelling month (related to temperature) as a covariate for detection probability (see below).…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation